Urinary Incontinence in childhood - L. Szabó (Elsevier, 2024)
In childhood, all forms of adult urinary incontinence occur, only the underlying causes and their distribution may be different.Patients and Methods5725 children (aged 0-18 years) underwent urodynamic examination in the Velkey László Child Health Center, Miskolc, and in the Heim Pál National Pediatric Institute, Budapest between 1986 and 2023.Results: 675 children had urinary incontinence. 471/1335 children with nocturnal enuresis had non-monosymptomatic enuresis with urge incontinence. 115 children have dysfunctional voiding.Videourodynamic study showed overactive bladder dysfunction in 31 %, neurogenic bladder dysfunction in 7 %, urine outflow obstruction in 3 %, and vaginal reflux in 2 % children.Conclusion: The disorder of urinary retention and emptying occurs as a result of the disorder of the coordinated functioning of the bladder emptying muscle, the detrusor and the closing muscle group, the sphincter. Urge incontinence, overactive bladder function is the most common form of UI in childhood. Anamnesis and uroflow examination are sufficient to establish an accurate diagnosis. Unfortunately, anticholinergic medication is still the accepted treatment for children, with many side effects.Incontinence after urination is most often caused by vaginal reflux, which can be easily detected with a video urodynamic examination.Nocturnal enuresis is one of the most common problems in early childhood. Simple explanation, the bladder fills up at night, either because there is a lot of urine output at night, or because the bladder capacity is small. The next step is that the child does not wake up with a full bladder. He sleeps so deeply that he does not respond to the urge to urinate during sleep, and he wets the bed or wakes up and becomes a nocturnal urinates.Most childhood urinary incontinence can be successfully treated and resolved in childhood.